The application of logotherapy to improve the meaning of life in emerging adults with self-injury - Maurits, Reisha Hermana; Hatta, Muhammad Ilmi; Suhana, Suhana (University of Muhammadiyah Malang, 2023)
Self-injury occurs commonly in young people, especially during the development phase of emerging adults. It is seen as a manifestation of existential problems, such as obstacles in fulfilling or pursuing meaning in life which is the most basic human motivation. This study aims to determine the effect of logotherapy as an intervention to increase purpose in life in emerging adults who engage in self-injury. The research utilized a single case experiment A-B design involving two subjects, measuring their level of meaning in life with the Meaning in Life Questionnaire (MLQ). The analysis technique of visual analysis, baseline-corrected tau, and Reliable Change Index (RCI) yielded outcomes indicating logotherapy as an effective intervention option for increasing meaning in life in emerging adults with self-injury.